Autodesk 3ds max 2012 essentials - Derakhshani, Randi 546421; Derakhshani, Dariush 247565 (Indianapolis, Ind. : Wiley Pub.)
A guide to 3ds Max explains how to use the software to create a variety of animation, film effects, and games.